Genetic structure of the Painted Bunting and its implications for conservation of migratory populations. (16th August 2018) - Contina, Andrea; Alcantara, Jose L.; Bridge, Eli S.; Ross, Jeremy D.; Oakley, William F.; Kelly, Jeffrey F.; Ruegg, Kristen C.
Abstract : The Painted Bunting Passerina ciris is a Neotropical songbird which breeds primarily in the USA during the summer and migrates to Mexico, Central America, southern Florida and the Caribbean over the winter. Male Painted Buntings are brightly coloured, which makes them highly sought after as pets, particularly in Mexico, Central America and Europe. We used short sequence repeats (microsatellite DNA) to investigate the population genetic structure of the Painted Bunting and its implications in conservation management of migratory populations. We found a detectable level of population differentiation as revealed by pairwise F ST and R ST comparisons and Bayesian clustering analyses, with strong support for differentiation between eastern and western Painted Buntings (e.g. Oklahoma and Georgia F ST = 0.1; P = 0.005; R ST = 0.18; P = 0.04) in accordance with previous mitochondrial DNA analysis. We recovered additional support for two sub‐groups within the western clade. While linking migrant songbirds captured outside of the USA to their breeding populations remains a challenge, we show that natural levels of population genetic differentiation can be detected via microsatellite DNA markers and exploited in migratory connectivity studies. We also demonstrate the potential utility of our low‐cost markers for population identification of birds recovered from the pet trade by screening a small subset of samples ( n = 5) collected as part of wildlife tracking. We discuss the implications of our results for future efforts to understand patterns of population decline in Painted Buntings more generally, as well as how we might expand this methodology to combat illegal pet‐trade activity in this and other songbird species.